2022
DOI: 10.1055/s-0041-1740929
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Injury Mechanism and the Incidence of ACL Avulsions in Schatzker Type IV Tibial Plateau Fractures: A 3D Quantitative Analysis Based on Mimics Software

Abstract: Introduction Tibial plateau fractures are often accompanied with ligamental and meniscal injuries. Among which, the combined existence of Schatzker type IV fracture with anterior cruciate ligament (ACL) avulsion has been reported rarely. The purpose of this study was to determine the injury mechanism of Schatzker type IV fracture with ACL avulsion based on Mimics software. Methods Ninety-nine Schatzker type IV tibial plateau fractures were retrospectively analyzed by quantitative three-dimensional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Flexion-valgus pattern was the main cause of Schatzker type IV fractures associated with ACL avulsions. The findings will help orthopaedic surgeons understand the injury mechanism and augment their awareness of such injuries to avoid unfavourable prognosis (117).…”
Section: Residual Knee Instability Secondary To Ligaments Damage That...mentioning
confidence: 96%
See 1 more Smart Citation
“…Flexion-valgus pattern was the main cause of Schatzker type IV fractures associated with ACL avulsions. The findings will help orthopaedic surgeons understand the injury mechanism and augment their awareness of such injuries to avoid unfavourable prognosis (117).…”
Section: Residual Knee Instability Secondary To Ligaments Damage That...mentioning
confidence: 96%
“…Medial collateral ligament injury was the most common in the Schatzker type 2 (50% of the injuries) (116). According to Lin et al, tibial plateau fractures are often accompanied by ligamental and meniscal injuries (117). Among these, the combined existence of Schatzker type IV fracture with ACL avulsion has been published rarely.…”
Section: Residual Knee Instability Secondary To Ligaments Damage That...mentioning
confidence: 99%
“…The injury mechanism of tibial plateau fractures drew limited attention in previous studies 23 . Several literature had discussed the treatment or classi cation of tibial plateau fractures involving the injury mechanism, but the relevant content were oversimpli ed [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…MRI has been neglected as a tool in the evaluation of tibial plateau fractures. Recent studies have demonstrated its values in determining the mechanism of injury [ 70,71 ]. Modern Magnetic Resonance machines are capable not only to provide imaging of the soft tissue detail of the injury but will also provide information on the amount of damage to the cartilage and a surprising detail of associated bony injury.…”
Section: Discussionmentioning
confidence: 99%